2008
DOI: 10.3167/np.2008.120102
|View full text |Cite
|
Sign up to set email alerts
|

Cattle Breeding, Complexity and Mobility in a Structurally Unpredictable Environment: The Wodaabe Herders of Niger

Abstract: This paper explores the production strategy of a group of full-time mobile pastoralists from the perspective of their cattle-breeding system. The system is geared towards high reliability of good performance rather than towards maximizing peak productivity. At the core of the system is the organization of the cattle population along matriarchal lineages, for structuring animal diversity and ensuring the transmission of economically crucial functionality. The paper argues for a more sophisticated notion of past… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 36 publications
(29 reference statements)
0
29
0
Order By: Relevance
“…Unsurprisingly, given the lack of attention to leucism in camels in the scientific literature, no investigation has up to now been conducted on the genetics of piebald camels. From the information we collected, only a tentative hypothesis can be put forward, and in order to have a deeper understanding of piebald camels' genetics, a 'herd analysis exercise' (Krätli 2008) among herds including piebald camels would be helpful.…”
Section: Genetics Of Piebald Camelsmentioning
confidence: 99%
“…Unsurprisingly, given the lack of attention to leucism in camels in the scientific literature, no investigation has up to now been conducted on the genetics of piebald camels. From the information we collected, only a tentative hypothesis can be put forward, and in order to have a deeper understanding of piebald camels' genetics, a 'herd analysis exercise' (Krätli 2008) among herds including piebald camels would be helpful.…”
Section: Genetics Of Piebald Camelsmentioning
confidence: 99%
“…For example, some cattle prefer the pastures of the Logone Floodplain, whereas others prefer those of the Lake Maga area. These preferences develop over time as cattle are trained to graze specific species on specific pastures (Schareika 2003;Krätli 2008;Krätli and Schareika 2010). Because of habitude pastoralists are reluctant to change their habitual orbit because of the additional costs of animals that are not thriving on new pastures.…”
Section: Ideal Free Distribution Between Seasonal Grazing Areasmentioning
confidence: 99%
“…Early in the dry season water can be found throughout the floodplain, then only in depressions and rivers, and finally only in the rivers. In general, cattle graze more intensively when there is more and better forage (Krätli 2008;Schareika 2003). Grazing intensity is thus a function of forage quality and quantity.…”
Section: Developing a Diachronic Model Of Grazing Pressurementioning
confidence: 99%
“…Others have documented the in-depth knowledge that pastoralists have of their environment and how this shapes their everyday grazing strategies (Bollig and Schulte 1999;Krätli 2008: Schareika 2003. Bollig and Schulte (1999), for example, have shown that pastoralists' knowledge of their environment is fine-grained and complex and built up around the interaction between herds and vegetation.…”
Section: Introductionmentioning
confidence: 98%